Speculations 3 - Austin, Michael; Gironi, Fabio; Jackson, Robert; Ennis, Paul J.; Gokey, Thomas; Austin, Michael; Gironi, Fabio; Jackson, Robert; Ennis, Paul J.; Gokey, Thomas (Brooklyn, NY punctum books, 2012)
In this third volume of Speculations, a serial imprint created to explore post-continental philosophy and speculative realism, a wide range of topics are covered, from the philosophy of religion to psychoanalysis to the philosophy of science to gender studies, and in a wide variety of formats (articles, interviews, position pieces, translations, and review essays).
English
Keywords: Western philosophy, from c 1900 -; philosophy; speculative realism; object-oriented ontology